2021
DOI: 10.3390/nu13082778
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Worldwide Consumption of Ultra-Processed Foods: Findings and Criticisms

Abstract: A debate is ongoing on the significance and appropriateness of the NOVA classification as a tool for categorizing foods based on their degree of processing. As such, the role of ultra-processed food (UPF) on human health is still not completely understood. With this review, we aimed to investigate the actual level of consumption of UPF across countries and target populations to determine the impact in real contexts. Suitable articles published up to March 2021 were sourced through the PubMed and SCOPUS databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 126 publications
4
93
0
1
Order By: Relevance
“…), which could lead to potential selection biases and poor representativeness of a certain country. However, when compared with worldwide evaluations of UPF consumption, the presented results are reasonably consistent and comparable [47]. For instance, a study conducted on 740 Brazilian rural farmers reported that the largest caloric contribution to their diet was provided by minimally processed foods (64.7%), while UPFs contributed only minimally (5.2%); however, a higher dietary share of UPFs led to a lower intake of all macro-and micronutrients, without a distinction between healthy and unhealthy ones [48].…”
Section: Discussionsupporting
confidence: 74%
“…), which could lead to potential selection biases and poor representativeness of a certain country. However, when compared with worldwide evaluations of UPF consumption, the presented results are reasonably consistent and comparable [47]. For instance, a study conducted on 740 Brazilian rural farmers reported that the largest caloric contribution to their diet was provided by minimally processed foods (64.7%), while UPFs contributed only minimally (5.2%); however, a higher dietary share of UPFs led to a lower intake of all macro-and micronutrients, without a distinction between healthy and unhealthy ones [48].…”
Section: Discussionsupporting
confidence: 74%
“…A recent prospective cohort by Ferriero et al [ 21 ] indicated an inverse association between UPFs consumption and all-cause mortality. However, according to the conclusion of a systematic review performed by Marino et al [ 11 ], since most of the observations about UPF consumption were derived from studies conducted with food questionnaires which are not explicitly validated for such foods, further efforts are essential to confirm the previously obtained results regarding consumption of UPFs and risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the consumption of UPFs accounts for approximately 25–60% of total energy intake using individual-level data [ 7 , 8 , 9 , 10 ]. UPF energy consumption was highest in the USA and the United Kingdom, while the lowest levels were found in Italy [ 11 ]. UPFs comprise a large proportion of almost all ingredients derived from foods and additives, with little or even zero whole-food content.…”
Section: Introductionmentioning
confidence: 99%
“…Both those in favour of limiting UPFs [ 63 ], and those against the NOVA classification [ 64 , 65 , 66 ], acknowledge that the nutritional quality of UPFs is an important factor. Even some proponents of NOVA and reducing UPF intake have suggested that the saturated fat, added sugar and sodium content of UPFs is important, despite this not being a core aspect of the UPF definition [ 28 ].…”
Section: Upf Removal or Upf Reformulation: The Case For ‘Healthy’ Upfs?mentioning
confidence: 99%